The Sandwich Generation: Family Responsibilities and Individual Well-Being - Faiz Muhammad Kautsar; Salsa Azzahra Irvanianto; Diny Tri Agustin; Aghnia Dian Lestari (Journal of World Science, 2025)
This study aims to determine the impact of the dual role of the sandwich generation on the psychological well-being of individuals entering adulthood in Cirebon City who care for parents and fulfill family responsibilities. The main focus is on strategies and efforts to maintain a balance between family responsibilities and personal well-being, in order to achieve a more balanced and harmonious life. This study used a qualitative method with a phenomenological approach to understand the subjective experiences of individuals entering adulthood 20-30 years old as a sandwich generation in Cirebon City. In-depth interviews were conducted to explore the emotions, expectations, and challenges faced by individuals when caring for their parents and siblings, as well as how they manage their personal health while carrying out these dual roles. The results of this study showed that some informants were forced to take on the role of the sandwich generation due to family demands. This study shows that the sandwich generation faces great challenges in balancing the role of caring for parents and younger siblings with personal well-being. Although their responsibilities are different, good communication skills and stress management strategies, such as taking time for themselves, are both helpful. They hope to create financial stability and a more equitable division of responsibilities.